Effects of Binders on Shaped Nickel Catalyst Supported on ZEOLITE 5A - แพงไธสง, สุวัฒน์; สร้อยสุวรรณ, สร้อยพัทธา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
Two types of binders were selected for shaping the catalyst: Type I, consisting of methylcellulose (MC) and polyvinyl alcohol (PVA) at a 7:3 ratio by weight, and Type II, glutinous rice flour (GF). These were tested to compare the effects of binder decomposition on, or its benefits to, the carbon dioxide methanation (CO2 Methanation) process, which utilized a nickel metal catalyst on a Zeolite 5A support.           In the experiment, the catalyst was shaped into cylinders with a catalyst-to-binder ratio of 9:1 by weight. The tests were conducted using a plug flow reactor (PFR) in the temperature range of 200-500 °C at atmospheric pressure. Either 1 gram of the shaped catalyst or 0.1 grams of the pure binder was used under the feed conditions of pure nitrogen or hydrogen, and a carbon dioxide to hydrogen ratio of 1:4 at a flow rate of 60 milliliters per minute.           From the Thermogravimetric Analysis (TGA), it was found that both types of binders could decompose into carbon dioxide (CO2) in the range of 10-7 – 10-6 mol/min, carbon monoxide (CO) in the range of 10-6 – 10-5 mol/min, and methane (CH4), ethane (C2H6), and propane (C3H8) at 10-6 mol/min, 10-7 mol/min and 10-7 mol/min, respectively, through hydrogenolysis and pyrolysis reactions. However, the amount of gas produced was extremely small compared to the products generated from the methanation reaction of the nickel catalyst. For the tests conducted under a mixed gas of carbon dioxide and hydrogen, it was found that the Type I binder promoted carbon monoxide formation at a level of 10-4 mol/min, compared to 10-5 mol/min for Type II, via the reverse water-gas shift (RWGS) reaction at high temperatures. When combined with the nickel metal catalyst, it could continuously catalyze carbon monoxide methanation (CO Methanation), resulting in an increased methane yield. Therefore, the Type I shaping binder is more effective catalytically; however, in terms of mechanical shaping strength, it is not comparable to Type II.